2020
DOI: 10.1186/s12879-020-05140-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, vaccine effectiveness, and risk factors for mortality for pneumococcal disease among hospitalised adults in Singapore: a case-control study

Abstract: Background: Streptococcus pneumoniae infections can lead to severe morbidity and mortality, especially in patients with invasive pneumococcal disease (IPD). This study evaluated factors associated with pneumococcal disease, pneumococcal vaccine effectiveness, and risk factors for all-cause mortality in hospitalised adults with pneumococcal disease in Singapore. Methods: Retrospective case-control study of patients tested for pneumococcal disease with streptococcal urinary antigen testing and at least one steri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“… 13 37 IPD can lead to significant mortality and morbidity. 44 Our study showed decrease in incidence and trend of IPD and were statistically significant. The decrease in mortality of IPD during the COVID-19 pandemic was statistically insignificant, which can be contributed by the relative small sample size.…”
Section: Discussionsupporting
confidence: 51%
“… 13 37 IPD can lead to significant mortality and morbidity. 44 Our study showed decrease in incidence and trend of IPD and were statistically significant. The decrease in mortality of IPD during the COVID-19 pandemic was statistically insignificant, which can be contributed by the relative small sample size.…”
Section: Discussionsupporting
confidence: 51%
“…In this study, the median age of all patients was 31 years and the percent of patients between <16 years and 16–60 years groups are similar (40.16% vs 40.94%), while the percentage of patients older than 60 years old is low (18.9%). Many previous studies have described a higher level of pneumococcal disease among adult patients over the age of 65 and children younger than 5 years old [ 21 23 ]. This could be explained by the fact that our hospital is a comprehensive teaching hospital that houses various specialist wards to accept more adults with underlying diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum age of patients in this study is 1 day, however other studies reported the minimum age was 60 days or 6 months [ 24 , 25 ]. Underlying diseases have been reported as the risk factors for IPD [ 21 , 26 ], and reported underlying diseases including myocardial infarction, cerebrovascular disease, diabetes mellitus, malignancy, and so on. Our findings showed that 75 (59%) patients had some form of underlying diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Furthermore, a case-control study found that the case fatality rate for IPD was 26.1%, in contrast to a 11.4% case fatality rate for noninvasive pneumococcal infections. 42 The recommendation of PPSV23 as the mainstay vaccine for IPD may also be significant. 5 Specifically, the inconsistent findings regarding its effectiveness against pneumococcal pneumonia may have contributed to the focus of IPD in recent studies.…”
Section: Paradigm Shift In Pneumonia Management and Future Vaccinatio...mentioning
confidence: 99%